Recent Advances in Bone Tumours and Osteoarthritis - Amarasekera, Hiran (IntechOpen, 2021)
This book is a combination of recent advances in two major areas of orthopaedics: Bone tumours and Osteoarthritis. All chapters are contributed by well-known researchers and surgeons in Orthopaedics working across the globe. The book is divided into two major parts for clarity. All authors have contributed their original research, their experience in the field, and the recent advances that will keep the reader well informed and up to date in our understanding of bone tumours and osteoarthritis. This is a "must have" reference book for any medical library or an individual who is keen to update and have CME (continuous medical education) points added to their learning.